Occurrence of Phytophagous Scarabaeidae (Coleoptera) in a pasture area at the Balsamo municipality, São Paulo, Brazil - Terradas Menis, Flavio; Rodrigues, Sérgio Roberto (EntomoBrasilis, 2021)
Pasture areas have been decreasing over the years in Brazil, largely due to the expansion of agricultural areas, mainly in the Southeast region. Natural or planted pastures are subject to attack by insects that can become pests depending on their level of infestation and among them are the Scarabaeidae beetles. The scarce information on the species of this family existing in the region of Bálsamo (São Paulo) makes a study on the occurrence of these species necessary, thus generating data that can contribute to identification and information on possible existing pest species. During September 2018 to August 2019, collections of phytophagous Scarabaeidae species were done in pasture areas with a light trap. A total of 446 adults from the subfamilies Dynastinae, Melolonthinae and Rutelinae were collected. In Dynastinae the genera Bothynus, Coelosis, Cyclocephala, Chalepides and Actinobolus were collected, in Melolonthinae the genera Plectris and Liogenys and in Rutelinae the genera Anomala, Geniates, Leucothyreus, Lobogeniates, Byrsopolis and Trizogeniates were found. Among the species collected, some are described as pests in crops, including pastures, such as Liogenys suturalis Blanchard, which was the species that had the largest number of individuals during the collection period, being indicated as a species worthy of more detailed studies.